INVENTORY ANALYSIS OF A MULTISPECIALTY MEDICAL CLINIC IN BANDUNG - Fadli, Aulia
A multispecialty mother and child clinic in Bandung has a business issue where they could not achieve the Key Performance Indicator (KPI) target of 15 days in Inventory every month from July 2018 to June 2019. This KPI aims monitor the performance of the inventory. The current Days in Inventory average is 21 days. DII is influenced by 3 factors which are the inventory system, demand forecasting and operational process. The inventory process starts at the finance unit doing planning and demand forecasting, then to the pharmacy unit who procure from suppliers, and then manage the inventory depot, then the medical unit will prescribe and use items from in inventory, and the patient could receive needed service and medicine. Several root causes are found which results in high inventory cost and increases the Days in Inventory. First is the mismatch of stock optimization model and the procurement model. The stock level optimization uses the Q-model to have a fixed order quantity. However, the procurement is done weekly which are closer to the fixedtime period model or the P-model. The next root cause is the unoptimized forecasting